Finite element poroelastic modelling of brain oedema formation after ischaemic stroke reperfusion - Mohd Jamil Mohamed, Mokhtarudin; Aina Najwa, Nadzri; Stephen, Payne (Universiti Malaysia Pahang, 2019)
One of the risks of ischaemic stroke reperfusion treatment is the formation of brain oedema. This is usually observed clinically by the formation of herniation, which if not treated, it may disrupt brain functionality. In this paper, a mathematical model of brain oedema formation after stroke has been developed and simulated on an ideal 3D brain geometry with different infarct sizes and locations, to see their effects on brain herniation. The brain tissue displacement and pressure are then analyzed. It is found that those infarcts with large sizes and located nearer to the brain ventricle cause severe brain herniation.